Recognition for university - Ong, Han Sean (The Star Publications (M) Berhad, 2018)
Kuantan: Universiti Malaysia Pahang (UMP) has bagged the QS 5-star ratings award in the Quacquarelli Symonds (QS) Star Rating System 2018 in the recently conducted QS Stars audit.